2021
DOI: 10.37989/gumussagbil.848507
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Individuals' Coronavirus Anxiety Levels on Their Psychological Resilience

Abstract: Bu çalışmanın amacı; COVID-19 salgını sürecinde Türkiye’de yaşayan bireylerin sosyo demografik özellikleri ile koronavirüs anksiyete düzeyleri ve psikolojik sağlamlıkları arasındaki ilişkinin incelenmesidir. Kesitsel ve tanımlayıcı tipte olan çalışmanın evrenini, araştırmaya katılmayı kabul eden 15 yaş üstü bireyler oluşturmaktadır. Araştırma kapsamında 425 bireye ulaşılmıştır. Araştırmanın verileri çevrimiçi anket yöntemi (Google Forms aracılığıyla) ile toplanmıştır. Veri toplama aracı olarak; araştırmacıları… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Coronavirus anxiety appears to have negative effects not only on young people but also on older individuals. Studies conducted on adults have reported that as coronavirus anxiety increases, the level of hopelessness increases (Yılmaz et al, 2020) whilst occupational performance levels (Hoşgör et al, 2020) and productivity at work (İri & Korkmaz, 2020) decrease. However, it has also been shown that the intensity of coronavirus anxiety symptoms is also important.…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus anxiety appears to have negative effects not only on young people but also on older individuals. Studies conducted on adults have reported that as coronavirus anxiety increases, the level of hopelessness increases (Yılmaz et al, 2020) whilst occupational performance levels (Hoşgör et al, 2020) and productivity at work (İri & Korkmaz, 2020) decrease. However, it has also been shown that the intensity of coronavirus anxiety symptoms is also important.…”
Section: Discussionmentioning
confidence: 99%